Post-Translational Modifications of Proteins: Novel Insights in the Autoimmune Response in Rheumatoid Arthritis - Francesco Carubbi; Alessia Alunno; Roberto Gerli; Roberto Giacomelli (Cells, 2019)
Post-translational modifications (PTM) are chemical changes mostly catalyzed by enzymes that recognize specific target sequences in specific proteins. These modifications play a key role in regulating the folding of proteins, their targeting to specific subcellular compartments, their interaction with ligands or other proteins, and eventually their immunogenic properties. Citrullination is the best characterized PTM in the field of rheumatology, with antibodies anticyclic citrullinated peptides being the gold standard for the diagnosis of rheumatoid arthritis (RA). In recent years, growing evidence supports not only that a wide range of proteins are subject to citrullination and can trigger an autoimmune response in RA, but also that several other PTMs such as carbamylation and acetylation occur in patients with this disease. This induces a wide spectrum of autoantibodies, as biomarkers, with different sensitivity and specificity for diagnosis, which may be linked to peculiar clinical manifestations and/or response to treatment. The purpose of this review article is to critically summarize the available literature on antibodies against post-translationally modified proteins, in particular antibodies against citrullinated proteins (ACPA) and antibodies against modified proteins (AMPA), and outline their diagnostic and prognostic role to be implemented in clinical practice for RA patients.